Keratinized gingival repair stent
By designing asymmetric bilayer structure keratinized gingival repair stent, the problems of long time, large pain and tissue mismatch of soft tissue incremental surgery in periodontal surgery are solved, and effective promotion of tissue regeneration and repair in periodontal surgery is achieved and the effect of protecting wounds.
Patent Information
- Application Number
- CN202323629461.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2033-12-29
AI Technical Summary
The existing periodontal surgery for soft tissue increments have problems such as long surgery time, postoperative pain and discomfort, limited tissue volume, and mismatch of postoperative increments with surrounding soft tissues.
Design a keratinized gingival repair scaffold with an asymmetric bilayer structure, including a loose layer and a dense layer. The loose layer is a porous sponge structure, and the dense layer is an animal-derived patch. It is connected by an adhesive layer, and silver-doped biological is added to the material. Active glass particles to improve antibacterial and pH regulation capabilities.
The stent protects wounds in an open healing environment, promotes tissue regeneration and repair, has high water absorption and high circulating load volume retention, can withstand complex mechanical forces in the oral cavity, and has low immunogenicity.
Smart Images

Figure CN222510563U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the technical field of biomedical materials, in particular to a keratinized gingival repair bracket. Background Art
[0002] Insufficient periodontal soft tissue has always been one of the urgent problems to be solved in the field of periodontology and implants. Patients suffer from periodontal soft tissue recession due to traumatic brushing, improper subgingival restorations, and periodontitis. The amount of soft tissue around the implant is directly related to whether the implant can resist plaque accumulation. At the same time, sufficient keratinized gingiva tightly combined with the implant can reduce the occurrence of peri-implant inflammation and prevent implant loosening. At present, the surgeries used for soft tissue augmentation in periodontal surgery are mainly: autologous connective tissue transplantation and free gingival transplantation technology. Autologous connective tissue transplantation usually cuts a certain size and depth of grafts from the palatal donor area, and the increase of the second surgical area means increased operation time and postoperative pain and discomfort for patients, especially when the defect involves multiple teeth and the defect range is large. The limited amount of tissue in the palatal donor area is difficult to meet the needs of the operation. When the donor area extends to the first molar on the palatal side, it is possible to touch the greater palatine artery; and the keratinized gingiva augmented after surgery retains the characteristics of the original donor area, which often does not match the color and texture of the surrounding soft tissue.
[0003] Existing keratinized gingival scaffolds Therefore, it is of great significance to design a keratinized gingival biological scaffold with low immunogenicity, which can protect wounds and effectively promote tissue regeneration and repair. Utility Model Content
[0004] In view of the above situation, in order to make up for the defects of the existing keratinized gingival repair stent, the utility model provides a keratinized gingival repair stent, which has low immunogenicity, can protect the wound in an open healing environment and effectively promote tissue regeneration and repair.
[0005] The technical solution of the utility model to solve the problem is as follows:
[0006] A keratinized gingiva repair stent, the stent is an asymmetric double-layer structure, including a loose layer and a dense layer, the loose layer is a porous sponge structure, and the dense layer is an animal-derived patch; wherein the loose layer is in contact with a wound surface.
[0007] In some embodiments of the present invention, the thickness of the loose layer is 0.5 to 2.5 mm; the thickness of the dense layer is 0.01 to 0.5 mm.
[0008] In some embodiments of the present invention, the pore size of the loose layer is 10 to 300 μm.
[0009] In some embodiments of the present invention, the loose layer and the dense layer are bonded by cross-linking.
[0010] In some embodiments of the present invention, the material of the loose layer is a biopolymer material added with silver-doped bioactive glass particles.
[0011] In some embodiments of the present invention, the material of the loose layer is selected from any one or a combination of collagen, silk fibroin, hyaluronic acid or chitosan.
[0012] In some embodiments of the present invention, the animal-derived patch is selected from any one or a combination of porcine bladder basement membrane, porcine small intestinal submucosa, bovine pericardium or acellular dermal matrix.
[0013] In some embodiments of the present invention, the loose layer and the dense layer are bonded via an adhesive layer.
[0014] Compared with the prior art, the utility model has the following beneficial effects:
[0015] 1. The keratinized gingival repair stent provided by the utility model has a double-layer structure. The loose layer is a porous sponge structure, which is conducive to the formation of blood clots in the tissue and creates conditions for wound healing. The dense layer is an animal-derived patch structure, which can protect the wound in an open healing environment and allow tissue to adhere. The stent has a high water absorption rate, can promote wound healing, has a high cyclic loading volume retention rate, and can well resist the complex mechanical forces in the oral cavity.
[0016] 2. The keratinized gingival repair stent provided by the utility model, the material of the loose layer is a biopolymer material added with silver-doped bioactive glass particles, the silver-doped bioactive glass particles have antibacterial and pH dual regulating effects, which can not only effectively promote the regeneration and repair of oral soft tissue, but also balance the oral flora and pH microenvironment, and inhibit the growth and reproduction of harmful oral bacteria. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the cross-sectional structure of a keratinized gingival repair bracket according to an embodiment of the utility model.
[0018] Figure 2 This is a scanning electron microscope image of the loose layer of the keratinized gingival repair stent according to an embodiment of the utility model.
[0019] Figure 3 This is a scanning electron microscope image of the dense layer of the keratinized gingival repair stent according to an embodiment of the utility model.
[0020] Figure 4 This is a cross-sectional scanning electron microscope image of a keratinized gingival repair stent according to an embodiment of the present invention.
[0021] Figure 5 This is a diagram showing the results of a cyclic compression test of a keratinized gingival repair stent according to an embodiment of the present invention.
[0022] Figure 6 This is a diagram showing the results of a liquid absorption experiment of a keratinized gingival repair stent according to an embodiment of the present invention.
[0023] Reference numerals:
[0024] 1 loose layer;
[0025] 2 compact layer;
[0026] 3 Adhesive layer. DETAILED DESCRIPTION
[0027] The specific implementation of the utility model is further described in detail below with reference to the accompanying drawings.
[0028] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the utility model, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size, without affecting the effects and purposes that can be achieved by the utility model, should still fall within the scope of the technical content disclosed by the utility model. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the utility model. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the utility model without substantially changing the technical content.
[0029] The utility model provides a keratinized gingival repair bracket, referring to Figure 1 The stent is an asymmetric double-layer structure, including a loose layer 1 and a dense layer 2, wherein the loose layer 1 and the dense layer 2 are connected by an adhesive layer 3; the loose layer 1 is a porous sponge structure, and the dense layer 2 is an animal-derived patch; wherein the loose layer 1 is in contact with the wound surface. The loose layer 1 in the utility model is a porous sponge structure, which is conducive to the formation of blood clots in the tissue after contacting the wound surface, creating conditions for wound healing; the dense layer is an animal-derived patch structure, which can protect the wound in an open healing environment and allow tissue attachment. After implantation, the keratinized gingival repair stent should maintain tissue volume stability for a sufficiently long time during the healing process, and must be able to withstand the complex mechanical forces caused by chewing, tongue movement, speech and tooth movement. The keratinized gingival repair stent in the utility model is an asymmetric double-layer structure, and the loose layer 1 and the dense layer 2 are connected by an adhesive layer 3. After 49 cycles of loading, it still has a volume retention of more than 75%, which can well resist the complex mechanical forces in the oral cavity.
[0030] In some embodiments of the present invention, the thickness of the loose layer 1 is 0.5-2.5 mm, and can be 0.5-1.0 mm, 1.0-1.5 mm, 1.5-2.0 mm or 2.0-2.5 mm according to different tissue increment requirements; the thickness of the dense layer 2 is 0.01-0.5 mm, and can be 0.01-0.05 mm, 0.05-0.10 mm, 0.10-0.15 mm, 0.15-0.20 mm, 0.20-0.25 mm, 0.25-0.30 mm, 0.30-0.35 mm, 0.35-0.40 mm, 0.40-0.45 mm or 0.45-0.50 mm.
[0031] In some embodiments of the present invention, the pore size of the loose layer 1 is 10-300 μm, which can be 10-50 μm, 50-100 μm, 100-150 μm, 150-200 μm, 200-250 μm or 250-300 μm. The pore size of the loose layer 1 in the present invention is closely related to the water absorption rate and compression fatigue performance of the stent. In the preferred range, the stent has a high water absorption rate and a high cyclic loading volume retention rate.
[0032] In some embodiments of the present invention, the loose layer 1 and the dense layer 2 are cross-linked, and a cross-linking agent is used to form a strong connection between the loose layer 1 and the dense layer 2, thereby improving the strength and rigidity of the stent and better resisting the complex mechanical forces in the oral cavity. In some specific embodiments of the present invention, the cross-linking agent is selected from any one or more of glutaraldehyde, carbodiimide or genipin.
[0033] In some embodiments of the utility model, the material of the loose layer 1 is a biopolymer material to which silver-doped bioactive glass particles are added. The biopolymer material has good biocompatibility and high mechanical strength, and has an important influence on the compression fatigue performance of the stent. The oral cavity is an environment with complex flora, and the symbiotic balance of the flora is crucial to maintaining the health of the gums. Unbalanced microorganisms change from the original symbiotic state to a pathogenic state, and invasive bacteria assist non-invasive bacteria to enter the gingival epithelial cells. The normal immune defense function of the gingival epithelial cells is destroyed, and they cannot resist bacterial invasion, and secrete a large amount of cytokines to cause immune damage. Silver-doped bioactive glass has good biocompatibility, has the ability to stop bleeding, promote the regeneration of alveolar bone and periodontal ligament, and can inhibit the retreat of periodontal epithelium. Silver-doped bioactive glass can release silver ions, and the surface of the bioactive glass is alkaline, which can maintain a neutral pH environment in the oral cavity, so that the growth of acid-producing bacteria such as Streptococcus mutans and bacteria with strong caries-causing properties is inhibited. The biopolymer material with silver-doped bioactive glass particles can be selected from commercial products or prepared according to published literature. Preferably, the mass fraction of silver-doped bioactive glass particles in the loose layer 1 is 0.01-1%. Specifically, the bioactive glass is selected from any one or a combination of 45S5, 77S, 13-93 or S53P4; the biopolymer material is selected from any one or a combination of collagen, silk fibroin, hyaluronic acid or chitosan.
[0034] In some embodiments of the present invention, the animal-derived patch is selected from any one or a combination of porcine bladder basement membrane, porcine small intestinal submucosa, bovine pericardium or acellular dermal matrix.
[0035] In some embodiments of the present invention, the adhesive layer 3 is selected from a biological adhesive and a hydrogel adhesive. Specifically, the biological adhesive is selected from a fibrin glue; the hydrogel adhesive is selected from a PEG gel, a GelMA gel, a polysaccharide gel, and the like.
[0036] Working principle: The keratinized gingival repair bracket provided by the utility model refers to Figure 1 to Figure 4The stent is an asymmetric double-layer structure, including a loose layer 1 and a dense layer 2, and the loose layer 1 and the dense layer 2 are connected by an adhesive layer 3; the loose layer 1 is a porous sponge structure, and the material used is a biopolymer material with silver-doped bioactive glass particles added, the dense layer 2 is an animal-derived patch, and the adhesive layer 3 uses a cross-linking agent. When in use, the loose layer 1 contacts the wound surface, and its porous sponge structure is conducive to the formation of blood clots in the tissue, creating conditions for wound healing, and the dense layer 2 can protect the wound in an open healing environment and allow tissue to adhere. Because the stent has a suitable water absorption rate and a high cyclic loading volume retention rate, it can well resist the complex mechanical forces in the oral cavity. The silver-doped bioactive glass in the material of the loose layer 1 can release silver ions. At the same time, the surface of the bioactive glass is alkaline, which can maintain a neutral pH environment in the oral cavity, inhibiting the growth of acid-producing and cariogenic bacteria such as Streptococcus mutans, and also has the ability to stop bleeding, promote the regeneration of alveolar bone and periodontal ligament, and inhibit the retreat of periodontal epithelium.
[0037] Compression test
[0038] The experimental process is as follows: first, the keratinized gingival repair scaffold provided by the utility model is immersed in a phosphate buffer solution at 37°C and pH=7.4 for 2 hours, and then a compressor is used to measure the percentage of the thickness w2 of the sample after 49 cycles of loading between 0.5 and 12.1 kPa relative to the initial thickness w1 of the first loading. The results are shown in Figure 5 shown.
[0039] The percentage of the initial thickness of the specimen after cyclic loading relative to the first loading
[0040] W represents the percentage of the initial thickness of the sample after cyclic loading relative to the first loading, w1 represents the initial thickness of the sample, unit: mm; w2 represents the thickness of the sample after 49 cycles of loading, unit: mm.
[0041] Depend on Figure 5 It can be seen that the keratinized gingival repair stent provided by the utility model still has a volume retention of more than 75% after undergoing 49 cycles of loading, and can well resist the complex mechanical forces in the oral cavity.
[0042] Water absorption test
[0043] The experimental process is as follows: take a certain mass of the keratinized gingival support sample provided by the utility model, accurately weigh it, and record it as m1. Immerse the sample in a beaker filled with 37±2℃ distilled water, completely soak it, and absorb it to saturation. Use tweezers to clamp one corner of the sample and take it out of the water. Hold the sample on the water surface with tweezers for 1 minute, drain the excess water, weigh it again, and record it as m2. Randomly sample 5 parts, and report the saturated water absorption multiple as the average value. The results are as follows Figure 6 shown.
[0044]
[0045] A represents the water absorption rate of the sample; m2 represents the mass of the sample after immersion in water, unit: g; m1 represents the mass of the sample before immersion in water, unit: g.
[0046] Depend on Figure 6 It can be seen that the keratinized gingiva repair bracket provided by the utility model has a water absorption rate of up to 1300%, and has good liquid absorption.
[0047] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the technology may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed in the present invention shall still be covered by the claims of the present invention.
Claims
1. A keratinized gingival repair stent, characterized in that: The stent is an asymmetric double-layer structure, comprising a loose layer (1) and a dense layer (2), wherein the dense layer (2) is an animal-derived patch; the loose layer (1) is a porous sponge structure, and the thickness of the loose layer (1) is 2.0-2.5 mm; when in use, the loose layer (1) contacts the wound surface.
2. The keratinized gingiva repair stent according to claim 1, characterized in that: The thickness of the dense layer (2) is 0.01 to 0.5 mm.
3. The keratinized gingiva repair stent according to claim 1, characterized in that: The pore size of the loose layer (1) is 10 to 300 μm.
4. The keratinized gingiva repair stent according to claim 1, characterized in that: The loose layer (1) and the dense layer (2) are bonded by cross-linking.
5. The keratinized gingiva repair stent according to claim 1, characterized in that: The material of the loose layer (1) is selected from any one of collagen, silk fibroin, hyaluronic acid or chitosan.
6. The keratinized gingiva repair stent according to claim 1, characterized in that: The animal-derived patch is selected from any one of porcine bladder basement membrane, porcine small intestinal submucosa, bovine pericardium or acellular dermal matrix.
7. The keratinized gingiva repair stent according to claim 1, characterized in that: The loose layer (1) and the dense layer (2) are bonded via an adhesive layer (3).
8. The keratinized gingiva repair stent according to claim 7, characterized in that: The adhesive layer (3) is selected from biological adhesives and hydrogel adhesives.